Purified Pyocyanin from Clinical Isolates of Pseudomonas aeruginosa Enhances Antibiotic Sensitivity Against Some Pathogenic Bacteria - Duaa Ghazi1 , Hasan Faisal Kahya2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Pseudomonas aeruginosa is one of the most life-threatening pathogen. It is considered nosocomialopportunistic microbe that cause wide range of infections including wound and burn infections, respiratoryinfections, and Otitis media. Despite the efficiency of antibiotics against infectious diseases, P. aeruginosastill causes complicated infections with antibiotic resistance in many clinical strains. The pigments producedby P. aeruginosa exhibits antibacterial properties. Thus, we have examined its ability to enhance antibioticseffect against some pathogenic microbes. 286 samples were collected from patients with different infectionswho visited Mosul hospitals. 76 samples were positive to P.aeruginosa. Among them, 38 (13.28%) of isolateswere isolated from surgical infection, whereas, 12 (4.19%), 11(3.84%), and 7(2.447%) were isolated fromOtitis media, Urinary tract infection, and pus, respectively. The pyocyanin in low concentrations showedsynergistic effect with some antibiotics against Staphylococcus aureus and Escherichia coli. E. coli becamesensitive to ciprofloxacin and nalidixic acid when mixed with 100 mg/ml pyocyanin. However, cloxacillindid not show any activity against Staph.aureus when mixed with 1 mg/ml and 6.25 mg/ml pyocyanin. Staphaureus became sensitive to nalidixic acid when mixed with 1 mg/ml pyocyanin.